The high-energy emission from HD 93129A near periastron. Issue 4 (5th May 2020) - del Palacio, S; García, F; Altamirano, D; Barbá, R H; Bosch-Ramon, V; Corcoran, M; De Becker, M; Hamaguchi, K; Maíz Apellániz, J; Munar Adrover, P; Paredes, J M; Romero, G E; et al.
ABSTRACT: We conducted an observational campaign towards one of the most massive and luminous colliding wind binaries in the Galaxy, HD 93129A, close to its periastron passage in 2018. During this time the source was predicted to be in its maximum of high-energy emission. Here we present our data analysis from the X-ray satellites Chandra and NuSTAR and the γ-ray satellite AGILE . High-energy emission coincident with HD 93129A was detected in the X-ray band up to ∼18 keV, whereas in the γ-ray band only upper limits were obtained. We interpret the derived fluxes using a non-thermal radiative model for the wind-collision region. We establish a conservative upper limit for the fraction of the wind kinetic power that is converted into relativistic electron acceleration, f NT, e < 0.02. In addition, we set a lower limit for the magnetic field in the wind-collision region as B WCR > 0.3 G. We also argue a putative interpretation of the emission from which we estimate f NT, e ≈ 0.006 and B WCR ≈ 0.5 G. We conclude that multiwavelength, dedicated observing campaigns during carefully selected epochs are a powerful tool for characterizing the relativistic particle content and magnetic field intensity in colliding wind binaries.